Pengaruh Proses Reviu Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Aan Juanda; Pigo Nauli (Jurnal Akuntansi dan Keuangan (JAK), 2018)
This study aimes to determine the effect of financial statements review on the quality of local financial statement reports with an understanding of the goverment accounting standards as a moderation variable. This research is a quantitative research, with survey method conducted through questionnaire. The population in this study are all inspectorate in all regions of the Province of Lampung. Respondents in this study are all functional officers and other officials who are members of the Review team at each inspectorate at all regions in Lampung Province. The result of data analysis shows that the process of review for local government financial statements has a positive effect on the quality of local government financial reports, and an understanding of the government accounting standards by APIP did not moderate the relationship between the review process with the quality of local government financial reports